2009 11th Electronics Packaging Technology Conference 2009
DOI: 10.1109/eptc.2009.5416473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the chiral vector influence on thermal conductivity of carbon nanotubes

Abstract: Current paper focuses on the influence of chiral vector on thermal conductivity of carbon nanotubes. The nonequilibrium molecular dynamic technique was implemented in commercially available software. The eleven single-walled CNTs of various chirality (from zigzag to armchair) was investigated. Moreover, the influence of length on CNTs thermal conductivity was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…As for chiral SWNTs, that the ones with a larger chiral angle are greater than the ones with a smaller chiral angle is fading compared with what is concluded in the previous simulations where the influence from chirality is still obvious. But this distribution tendency is close to what has been shown in the literature, [21] but it does not exclude the diameter effects, since the diameters of SWNTs were largely different in the literature. At the same time, when the tube length becomes longer, a thermal conductivity increase is much more signifi-083101-5 cant in Group D than in Group C, which is partially because of the larger-diameter dependence where nonlinear phonon collisions increase.…”
Section: Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…As for chiral SWNTs, that the ones with a larger chiral angle are greater than the ones with a smaller chiral angle is fading compared with what is concluded in the previous simulations where the influence from chirality is still obvious. But this distribution tendency is close to what has been shown in the literature, [21] but it does not exclude the diameter effects, since the diameters of SWNTs were largely different in the literature. At the same time, when the tube length becomes longer, a thermal conductivity increase is much more signifi-083101-5 cant in Group D than in Group C, which is partially because of the larger-diameter dependence where nonlinear phonon collisions increase.…”
Section: Propertiessupporting
confidence: 84%
“…But Zhang et al [20] concluded through their calculation results that the thermal conductivity of chiral SWNTs was lower than those of zigzag and armchair ones, and the thermal conductivity of a zigzag SWNT was the highest. Falat et al [21] indicated that chirality greatly affected thermal conductivity even though the changing relationship between them was not so clear. Generally speaking, the existing investigations have not come to a unanimous conclusion about the effect of chirality on the thermal conductivity of SWNTs and so, more work needs to be done to understand this effect.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations of heat transfer between graphene and organic phases including phenolic resin, C30 paraffin wax, carbon nanotube, octane and polymer [11][12][13][14][15][16][17][18] had been reported. Rao et al [19] reported molecular dynamics simulation results of self diffusion and heat capacity of n-alkane based phase change materials.…”
Section: Introductionmentioning
confidence: 99%